Professional web parts and custom controls with ASP.NET 2.0 - Vogel, Peter (Wiley Pub., 2006)
Professional Web Parts and Custom Controls with ASP.NET 2.0 . Web Parts are reusable components that extract data from existing Microsoft or non-Microsoft applications for use in ASP.NET Web pages; they can also be used to build user controls. Presents developers with an understanding of how Web Parts work and how they can be developed. Examines how to secure and integrate Web Parts into other Windows systems (SQL Server, Office, ASP.NET, Content Manager)